AMRRHC: Active Monitoring Round Robin with Holding Capacity Load Balancing Algorithm - Bhagyalakshmi; Malhotra, D (International Journal of Computer Sciences and Engineering, 2025)
The cloud platforms are becoming popular day by day with the advent of more customers every second, flooding the cloud environment with millions of requests thereby making the processing of such requests a major challenge to be handled. The major goal of cloud computing is to provide requested resources efficiently and effectively which can be achieved by distributing the load in a balanced manner among various nodes leaving the network in an optimal condition. In this research paper, much optimized load balancing scheme has been proposed to schedule the tasks in the cloud environment. The scheme has been designed to calculate the load on the list of available Virtual Machines (VM), considering the CPU utilization and usage as a metric for calculation of load. The proposed scheme modifies the already existing Active Monitoring Load balancing algorithm and merges the advantages of Active Monitoring Load Balancing and dynamic Round Robin scheduling techniques.